Respuesta a la fertilización de la teca (Tectona grandis L.f) con NPK en ultisoles de la zona norte de Costa Rica - Fallas-Zuñiga, Juan Luis (Instituto Tecnológico de Costa Rica, 2014)
Although teak is widely used in the Northern Zone of Costa Rica in reforestation projects, there is no data in the tropics for calculating fertilization needs in Ultisols, mainly between plantation ages of 5 to 15 years old. Thus arises the objectives to determine the response to fertilization and quantify the increase in growth produced by the application of soil amendments and their economic benefit. The study was conducted in teak plantations aged between 0.79; and 11.17 years old. Was obtained in plantations under 2 years old, trees take the N directly of the soil. Between 3 and 7 years of age the largest increases are 220g of N in diameter and 80 g N in height and between 9 and 11 years old with 160 g N. For P, in diameter in plantations under 2 years old no answer. Between 3 and 11 years treating 300 g outperforms all treatments. For the K, in the diameter in the first stage, the best treatment was 220 g. In the second stage, there was no difference. In third stage, the witness outperforms all treatments. In stage four the best was 160 g. There are
Proyecto de Graduación (Licenciatura en Ingeniería Forestal). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2014.
Keywords: Reforestación; Plantaciones; Valor económico; Suelos; Madera